2022
DOI: 10.1024/0300-9831/a000728
|View full text |Cite
|
Sign up to set email alerts
|

Improving vitamin D status in bariatric surgery subjects with monthly high-dose ergocalciferol

Abstract: Abstract. Background: Vitamin D insufficiency is common before and after bariatric surgery. Optimal supplementation to treat vitamin D insufficiency is not clearly defined. Objective: Determine if serum 25 (OH) D levels improve by the consumption of an additional monthly ergocalciferol supplement by subjects after bariatric surgery. Study design: Thirty-two subjects were randomly divided to receive an additional 100,000 IUs of ergocalciferol monthly after bariatric surgery (n=10) or standard level vitamin D su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…Foi feita uma revisão de literatura nas bases de dados PubMed, BVS e SciElo os descritores "Surgeri Bariatric" and "Hypovitaminosis" and "Nutrient Outra estratégia significativa foi a administração de 2 doses mensais de 50.000 UIs de ergocalciferol em adição aos polivitamínicos demonstrou aumento dos níveis séricos de 25 (OH) D no período de 1 ano da cirurgia em comparação aos tratados apenas com polivitamínicos (GALYEAN et al, 2021).…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…Foi feita uma revisão de literatura nas bases de dados PubMed, BVS e SciElo os descritores "Surgeri Bariatric" and "Hypovitaminosis" and "Nutrient Outra estratégia significativa foi a administração de 2 doses mensais de 50.000 UIs de ergocalciferol em adição aos polivitamínicos demonstrou aumento dos níveis séricos de 25 (OH) D no período de 1 ano da cirurgia em comparação aos tratados apenas com polivitamínicos (GALYEAN et al, 2021).…”
Section: Metodologiaunclassified
“…A média de idade entre as publicações variou de 37,7 anos (MUSELLA et al, 2022) a 50,9 anos (GALYEAN et al, 2021). Diferentes técnicas em cirurgia bariátrica foram avaliadas em cada publicação, sendo as mais prevalentes RYGB (8 trabalhos) e SG (5 trabalhos).Outras estratégias avaliadas foram LGS (2 trabalhos), derivação biliopancreática(GALYEAN et al, 2021), banda gástrica ajustável(SILVA et al, 2016) e VLRL-RYGB(Leeman et al, 2020). Apenas LGS foi estudada de maneira isolada, porElhag et al (2017) e por Sen O et al (2022).…”
unclassified
“…According to the US Endocrine Society, serum 25(OH)D deficiency is characterized by values <20 ng/mL (50 nmol/ L), insufficiency as serum 25(OH)D between 21 and 29 ng/ mL (51-74 nmol/L), and sufficiency as ≥30 ng/mL (75 nmol/L) [5,7,9]. In contrast, the Institute of Medicine says that serum 25(OH)D ≥20 ng/mL (50 nmol/L) is sufficient to cover the needs of 97.5% of the population, and overt deficiency occurs when 25 (Serum OH) D is <12 ng/mL (30 nmol/L) [10].…”
Section: Bariatric Surgeries and Nutrient Deficienciesmentioning
confidence: 99%
“…Some guidelines recommend a vitamin D supplementation of at least 3,000 IU per day and titration to the therapeutic dose when reaching sufficient serum levels and showing improvement, in parallel, several studies have shown that bariatric surgery patients (RYGB and BPD) had a significant increase in 25 OH D after receiving an additional monthly oral dose of 100,000 IU ergocalciferol for one year after bariatric surgery. [5,7,9,15]. Most studies agree that a daily dosage below 800 IU of vitamin D3 is not sufficient to treat hypovitaminosis D in bariatric patients, and other studies have suggested the use of a combination of 50,000 IU of vitamin D2 weekly, in addition to a daily dose [1,4].…”
Section: Vitamin D Supplementationmentioning
confidence: 99%
See 1 more Smart Citation